Perioperative Clinical Usage of Phellinus Linteus as a Nutraceutical for Non-FOLFIRINOX-Based Postoperative Adjuvant Chemotherapy for Resected Pancreatic Cancer: A Retrospective Cohort Study - Juwan Kim MD; Seung Soo Hong MD; Sung Hyun Kim MD, MS; Ho Kyoung Hwang MD, PhD; Chang Moo Kang MD, PhD (Integrative Cancer Therapies)
Introduction: Most patients with pancreatic cancer experience systemic recurrence within 1 to 2 years after radical pancreatectomy. Phellinus linteus (PL) has demonstrated anti-inflammatory, antioxidant, and anti-cancer properties, suggesting potential as an adjunct to cancer therapy. This study aimed to evaluate the long-term oncological impact of perioperative PL in resected pancreatic cancer. Method: This retrospective cohort study included 407 patients who underwent curative resection and adjuvant chemotherapy for pancreatic cancer at Severance Hospital (2012-2022). Among them, 103 patients who began PL postoperatively and continued throughout treatment were assigned to the PL group; 304 patients without PL intake comprised the control group. Results: The mean overall survival (OS) was significantly longer in the PL group (47.0 months; 95% CI: 42.8-51.1) than in the control group (35.0 months; 95% CI: 30.3-39.7; P < .001). Recurrence-free survival (RFS) showed a borderline improvement ( P = .053). PL use was marginally associated with improved OS in multivariate analysis (HR: 0.614; 95% CI: 0.376-1.002; P = .051). Subgroup analysis showed no significant OS or RFS benefit with PL in patients receiving FOLFIRINOX. However, among patients treated with non-FOLFIRINOX regimens, PL use led to significantly better OS (43.9 months vs 35.0 months; P = .021), though RFS remained similar. Notably, the OS of the non-FOLFIRINOX + PL group was comparable to that of the FOLFIRINOX group ( P = .332) and superior to the non-FOLFIRINOX control group ( P = .021). Conclusion: PL may enhance survival in resected pancreatic cancer, particularly in patients receiving non-FOLFIRINOX chemotherapy, supporting its role as a potential adjunct when FOLFIRINOX is not feasible.